2010
DOI: 10.1093/imrn/rnm131
|View full text |Cite
|
Sign up to set email alerts
|

Relating Two Hopf Algebras Built from An Operad

Abstract: Starting from an operad, one can build a family of posets. From this family of posets, one can define an incidence Hopf algebra. By another construction, one can also build a group directly from the operad. We then consider its Hopf algebra of functions. We prove that there exists a surjective morphism from the latter Hopf algebra to the former one. This is illustrated by the case of an operad built on rooted trees, the NAP operad, where the incidence Hopf algebra is identified with the Connes-Kreimer Hopf alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 15 publications
1
54
0
1
Order By: Relevance
“…There is a group associated to each operad; see Appendix A and [Chapoton 2002a;2007/08;van der Laan 2003;Chapoton and Livernet 2007]. We will need the group G PL associated to the pre-Lie operad.…”
Section: The Reader Can Check This Statement On the Examples Of Figurmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a group associated to each operad; see Appendix A and [Chapoton 2002a;2007/08;van der Laan 2003;Chapoton and Livernet 2007]. We will need the group G PL associated to the pre-Lie operad.…”
Section: The Reader Can Check This Statement On the Examples Of Figurmentioning
confidence: 99%
“…This can also be found in [Chapoton 2002a;2007/08;van der Laan 2003;Chapoton and Livernet 2007]. We use in this section the definition of the notion operad by a multiple composition map γ , which is equivalent (using the unit) to the definition using the single compositions • i that we have used elsewhere in the article.…”
Section: Frédéric Chapotonmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these is a construction [vdL04] taking an operad O as input and producing a bialgebra H (O) as output, which is called the natural bialgebra of O. This construction has been studied in some recent works: in [CL07], it is shown that H can be rephrased in terms of an incidence Hopf algebra of a certain family of posets, and in [ML14], a general formula for its antipode is established. Let us also cite [Fra08] in which this construction is considered to study series of trees.…”
Section: Introductionmentioning
confidence: 99%